Análise em larga escala da senescência desencadeada por FGF-2 em células tumorais de camundongo da linhagem Y1 - Lopes, Mariana De Camargo [UNIFESP] (2019)
Despite being a growth factor, FGF-2 has anti-proliferative and tumor suppressive functions in some cellular contexts. In a murine adrenocortical tumor cell line that has the proto-oncogene K-Ras constitutively amplified and overexpressed (lineage Y1), FGF-2 triggers an initial mitogenic response through ERK1/2, PKC and AKT signaling that ultimately results in cell cycle arrest at the G2/M transition through RhoA/GTP-src signaling pathways. To better understand the dual phenotypic response (mitogenic versus cell cycle arrest) induced by FGF-2, we employed quantitative mass spectrometry to serially analyze histone PTMs and general protein phosphorylation in Y1 cells over time after treatment FGF-2 or serum alone. Despite their relevance to understanding the regulation of gene expression, large-scale analyses that connect signaling pathways to histone post-translational modification dynamics are lacking in the literature. We report that treatment of Y1 cells with FGF-2 induces effects that are in agreement with the phenomenon of oncogene-induced cell senescence, based on detection of heterochromatin foci formation with histone H1 depletion, silencing of cyclins and cyclin dependent kinase genes, DNA damage foci formation, lamin-B1 depletion and induction of a secretory phenotype containing interleukins and other soluble factors, such as IL-11 and PAI-1. Specifically, we observed a global decrease in markers of active chromatin regions, including histone H4 N-terminal acetylation and H3K27ac, and an increase in the abundance of the inactive chromatin marker H3K27me3, starting 3h after FGF-2 treatment. The hypothesis that FGF-2 induces alterations in chromatin structure, increasing the number of heterochromatin regions, was confirmed by electron microscopy. Subsequently, we integrated the data to obtain a systems biology perspective of the signaling pathways and epigenetic changes induced by serum and/or FGF-2. Moreover, our results indicate that FGF-2 treatment affects the phosphorylation dynamics of nuclear proteins related to transcription, as well as the abundance of proteins related to certain XVI biological processes, such as mitochondrial activity and translation. Having established that FGF-2 can alter transcriptional activity, we performed RNA-seq to identify genes and pathways affected by this growth factor, which may serve as candidates for future knockdown and overexpression studies to better understand the induction of senescence in tumor cells. We conclude that FGF-2 negatively affects pathways related to the cell cycle and reduces the abundance of the active chromatin marker H3K27ac near transcription start sites (TSS) of genes such as cyclin dependent kinase, cyclin A2 and cyclin B2, all of which are important for cell cycle progression. In addition, we observed that FGF-2 can induce a negative regulation of the MAPK pathway, increasing H3K27ac abundance near the TSS of the Dusp5 and Dusp6 genes, which are also upregulated transcriptionally and may relate to the phenotype discussed here. We believe that our work will shed light on how signaling pathways may interact with histone PTMs in both proliferative (serum stimulated cells) and non-proliferative (FGF-2 stimulated cells) responses.